Neighbourhood attachment and satisfaction: a Hong Kong's case study. Issue 1 (18th November 2020) - La Grange, Adrienne; Yau, Yung
Abstract : Purpose: This paper aims to study neighbourhood attachment and satisfaction in a middle-class, high-density and semi-gated neighbourhood in Hong Kong. Design/methodology/approach: Drawing on the findings of survey on 356 households, a principal component analysis and hierarchical regression analysis were conducted to assess how attachment and satisfaction were manifested and whether they were manifested as separate phenomena. Findings: Attachment and satisfaction in neighbourhoods were manifested as separate phenomena. It was further found that residents were broadly attached to and satisfied with their neighbourhood. Of the neighbourhood characteristics identified as influencing satisfaction in previous research, the support was found only for the physical environment and safety but concluded that satisfaction was also influenced by status, neighbourhood youths' ambition and schools. Contrary to the expectation, the authors did not find support for deeper social bonds as an element of satisfaction. The hierarchical regression analysis indicated that satisfaction may lead to increased attachment. Social implications: This study offers policymakers and housing managers' valuable insights into the management of increasingly large and complex residential neighbourhoods. It helps us understand which initiatives are likely to lead to greater attachment. Originality/value: Previous studies have focused on neighbourhood attachment and satisfaction in typical low/medium-density settings. This study extends previous efforts to a high-density housing estate of Hong Kong.